2018
DOI: 10.15253/2175-6783.2018193442
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the nursing students on stress-generating factors during the graduation

Abstract: Objective: to understand, according to the perceptions of the nursing students, the stress-generating factors during graduation. Methods: this is a qualitative study, developed with 236 undergraduate nursing students, in a Higher Education Institution. The production of information was carried out by a semi-structured instrument, processed by the Software Interface for Multidimensional Analyzes of Textes et de Questionnaires and submitted to Bardin content analysis. Results: six classes were created: the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Studies in the international scenario have shown frequently experienced stressful situations in the nursing training environment, such as the extensive curricular load, the lack of time for academic, social, family, physical and leisure activities, personal and family problems, dissatisfaction with public transport to the locations of practical activities, inflexible hours in institutions, difficulties in relationships with classmates and professionals in the activity areas (7)(8)(9) , in addition to lowering the students' commitment level to the course in the presence of high levels of stress (10) . Results from Brazilian studies also point to similar stressors (2,(4)(5)11) .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Studies in the international scenario have shown frequently experienced stressful situations in the nursing training environment, such as the extensive curricular load, the lack of time for academic, social, family, physical and leisure activities, personal and family problems, dissatisfaction with public transport to the locations of practical activities, inflexible hours in institutions, difficulties in relationships with classmates and professionals in the activity areas (7)(8)(9) , in addition to lowering the students' commitment level to the course in the presence of high levels of stress (10) . Results from Brazilian studies also point to similar stressors (2,(4)(5)11) .…”
Section: Introductionmentioning
confidence: 68%
“…Nursing students face several situations that trigger stress during their professional training period, such as their initial contact with the university and autonomy in organizing schedules (1) , curricular and extracurricular activities and the internship scenario, new relationships with teachers (2) , uncertain situations and making important decisions (3) .…”
Section: Introductionmentioning
confidence: 99%